2017
DOI: 10.1016/j.bbrc.2017.04.090
|View full text |Cite
|
Sign up to set email alerts
|

The LncRNA ZBED3-AS1 induces chondrogenesis of human synovial fluid mesenchymal stem cells

Abstract: Human synovial fluid-derived mesenchymal stem cells (SFMSCs) have great potential for cartilage induction and are promising for cell-based strategies for articular cartilage repair. Many long non-coding RNAs (lncRNAs) regulate chondrogenesis of MSCs. We hypothesized that the divergent lncRNA ZBED3-AS1, which binds locally to chromatin, could promote the expression of zbed3, a novel Axin-interacting protein that activates Wnt/β-catenin signaling, involved in chondrogenesis. However, the function of ZBED3-AS1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“… 41 Furthermore, lncRNA ZBED3-AS1 could activate Wnt/β-catenin signaling and stimulate chondrogenesis in human synovial-fluid-derived MSCs. 42 What is more, certain lncRNAs could be regulated by Wnt/β-catenin signaling during osteogenesis differentiation. A putative osteo-suppressing lncRNA HOTAIR was downregulated by Wnt/β-catenin signaling, which led to the upregulation of downstream osteogenic markers ALP and BMP2.…”
Section: Discussionmentioning
confidence: 99%
“… 41 Furthermore, lncRNA ZBED3-AS1 could activate Wnt/β-catenin signaling and stimulate chondrogenesis in human synovial-fluid-derived MSCs. 42 What is more, certain lncRNAs could be regulated by Wnt/β-catenin signaling during osteogenesis differentiation. A putative osteo-suppressing lncRNA HOTAIR was downregulated by Wnt/β-catenin signaling, which led to the upregulation of downstream osteogenic markers ALP and BMP2.…”
Section: Discussionmentioning
confidence: 99%
“…Ou et al studied that the lncRNA expression profile changed during induced cartilage differentiation process in hBMSCs, which suggested that 2166 lncRNAs were upregulated and 1472 lncRNAs were downregulated; the expression of ZBED3-AS1 (ZBED3 antisense RNA 1) and CTA-941F9.9 was verified by Q-PCR. These results indicate that lncRNAs are involved in MSC cartilage differentiation [ 68 ] ( Table 2 ).…”
Section: Lncrnas Involved In Chondrogenic Differentiationmentioning
confidence: 95%
“…Wang et al [53] demonstrated that the two lncRNAs may function in the early stage of chondrogenic differentiation. Further studies by Ou et al [54] found that ZBED3-AS1 could activate the Wnt/β-catenin signaling and increased the zbed expression. Overexpression of ZBED3-AS1 upregulates the expression levels of sox9 and collagen II, but the detailed mechanism requires further investigation.…”
Section: The Role Of Lncrnas In Cartilage Developmentmentioning
confidence: 95%